2001
DOI: 10.2106/00004623-200104000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Focal Osteolysis at the Junctions of a Modular Stainless-Steel Femoral Intramedullary Nail

Abstract: Background: During routine follow-up of patients treated with a three-piece stainless-steel modular femoral nail, osteolysis and periosteal reaction around the modular junctions of some of the nails were noted on radiographs. The purpose of this study was to evaluate the prevalence, etiology, and clinical relevance of these radiographic findings. Methods: Forty-four femoral fractures or nonunions in forty-two patients were treated with a modular stainlesssteel femoral intramedullary nail. Seventeen nails were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 20 publications
2
30
0
1
Order By: Relevance
“…Inflammatory mediators are released as a consequence of the cellular response to the particulate and/or ionic products of fretting and corrosion. This can ultimately result in the need to revise the prosthesis 10,11 . Recently, Varini et al reported that stem impactors that secure the femoral stem by means of the neck-stem junction induce some damage to the bore of the femoral stem.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory mediators are released as a consequence of the cellular response to the particulate and/or ionic products of fretting and corrosion. This can ultimately result in the need to revise the prosthesis 10,11 . Recently, Varini et al reported that stem impactors that secure the femoral stem by means of the neck-stem junction induce some damage to the bore of the femoral stem.…”
Section: Discussionmentioning
confidence: 99%
“…Patient was diagnosed with a periprosthetic fracture, a ''happy hip'' according to the Coventry classification (Vancouver type B1). 1,8,13 Medical history showed a hypertension for about 20 years, diabetes mellitus (oral medication), a cemented total hip arthroplasty on the left side in 1989, on the right side in 1992 and a total knee arthroplasty on the left side in 1993.…”
Section: Casementioning
confidence: 99%
“…5 Implant failures have been reported at modular interfaces. 4,7,8 Furthermore the presence of metal ions may trigger a foreign body response. 2,5,7,8 This foreign body response can lead to focal osteolysis and cortical thinning.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Ni 2þ produced in the corrosion process in the human body environment may cause cancer (Denkhaus and Salnikow, 2002;Vahter et al, 2002). On the other hand, particles released under friction conditions and repetitive contact can induce an environmental response that may lead to aseptic loosening due to osteolysis, which could lead to the subsequent implant failure (Hallab et al, 2002;Jones et al, 2001;Kowandy et al, 2006;Manley et al, 2002). The tangential micro-motion between the surface and the surrounding bone tissue may enhance the production of wear debris, thereby increasing the probability of failure.…”
Section: Introductionmentioning
confidence: 99%